Real-time hybrid simulation of full-scale tuned liquid column dampers to control multi-order modal responses of structures. (1st May 2017) - Zhu, Fei; Wang, Jin-Ting; Jin, Feng; Lu, Li-Qiao
Highlights: An RTHS framework is developed to carry out full-scale experiments of TLCD-structure-foundation systems. Using MTLCD to control multi-order modal responses of a 9-story benchmark building is comprehensively investigated. The SSI effect on TLCD performance is examined with consideration of both fixed and artificial boundaries. Abstract: This paper aims to demonstrate the real performance of tuned liquid column dampers (TLCDs) in controlling seismic response of multi-degree-of-freedom (MDOF) structures based on the advantages of real-time hybrid simulation (RTHS). An RTHS framework is developed to carry out full-scale experiments of TLCD-structure-foundation system, and the application of multiple TLCDs to control single-order and multi-order modal responses of a nine-story benchmark building is investigated, respectively, as an example. Moreover, the effect of soil–structure interaction (SSI) on TLCD performance is examined, in which the finite and semi-infinite soil flexible foundations are simulated through a finite element model with 1160 DOFs embedding fixed and artificial boundaries, respectively. Results show that MTLCD is more effective than a single TLCD in suppressing structural responses; and the former is suggested to be used to control multi-order modal responses because of the uncertainty of the frequency content of earthquake excitations. The SSI effect significantly reduces TLCD performance, and the semi-infinite foundation may eliminate the control effect of TLCD due to the radiation damping effect. The parameters of the TLCD device should be regulated according to the characteristics of SSI-structure system when the SSI effect is unneglectable.